PREDICTION OF DEPTH OF GROUNDWATER STREAM BELOW UNUSUAL GROWTH OF TWIGS OF NEEM AND TAMARIND TREES - BABASAHEB MORE (International Journal of Innovations in Engineering Research and Technology, 2021)
All plant growth is connected with solar lights. The trees grow symmetrical in shapes, but sometimes they are irregular. In the case of irregular shapes, some of the twigs of these trees are bent downward in a straight line. These bends of twigs will have some specific reasons. The trees, neem, tamarind, show such unusual growth. Some of the twigs of these trees are bent in the downward direction in a straight line. The Growth index ratio (GIR) with a growth index from the usual and unusual growth of the twigs of the same tree is calculated. The value of GIR greater than one indicates the presence of the stream below the unusual growth twigs of the tree. This unusual growth of trees is due to the increased gravitational force on these twigs. The GIR for different Neem and Tamarind trees were calculated, and depth of the stream at those particular twigs was measured. It is found that the plot between GIR of trees and Depth of the stream is a straight line. This suggests that the GIR of a tree is directly proportional to the depth of the stream present under that tree. In this paper, I propose to outline the body of research that gives a relation between GIR of trees and depth of the stream under that tree, which is useful for prediction of depth of stream by calculating GIR for that tree.